Mosque as Emergency Shelter in Natural Disaster: Responses and Challenges - Ashadi Cahyadi; Salim Bela Pilli; Ihsan Rahmat (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
Mosque has a pivotal role during the most critical phase in a natural disaster. However, mosque administrators frequently have no good comprehension of the other function of mosques other than a place of worship. When refugees of a natural disaster took shelter in the mosque, the mosque administrators were uncertain between keeping the mosque holiness as the house of God or prioritizing humanity first. This study discussed the responses and challenges of mosque administrators and refugees during making mosques as emergency shelters. This paper applied a qualitative approach to gather responses and challenges experienced by the administrators of Baiturrahim Mosque and a quantitative approach to survey why refugees chose the mosque as shelter. The value of this paper was to describe the different views of the mosque administrators regarding the function of the mosque, including the many challenges faced due to lack of knowledge and experience. Nine reasons why refugees chose mosques as shelters were assessed based on percentage. Refugees were faced with strict norms of decency and ethics from the mosque. Equalization of perceptions among administrators about the function of mosques and education to the community is essential in the mitigation phase. Therefore, we recommend the disaster authority make regulations and standard operating procedures to guide the work and direction of building mosques in disaster-prone locations for future preparation.